Health Information Through Electronic Media and External Reproductive Organ Hygiene in Adolescent Females - Muhammad Bagus Andrianto; Dewi Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the relationship between health information obtained through electronic media and personal hygiene of external reproductive organs in adolescent girls at SMK S 16 Pharmacy Bengkulu. The research method used was an observational analytical design with a cross-sectional approach. The results showed that most respondents had limited access to health information through electronic media and demonstrated poor personal hygiene practices of external reproductive organs. Bivariate analysis revealed a significant relationship between health information obtained through electronic media and personal hygiene of external reproductive organs. Adolescent girls who received inadequate health information through electronic media were more likely to have poor personal hygiene practices compared to those who received adequate information. In conclusion, there is a significant relationship between health information obtained through electronic media and personal hygiene of external reproductive organs in adolescent girls. Keywords: Health Information, Electronic Media, External Reproductive Organs, Adolescents